Effect of Bokashi Residue from Cow Dung and Oil Palm Empty Fruit Bunches on Soil Chemical Properties and Content of N. P, K and Mg palm plants After Two Years of Application - Nurseha Nurseha; Djatmiko Djamiko (University of Prof. Dr. Hazairin, SH, 2022)
The aim of this study was to examine the effect of bokashi residue from a mixture of cow dung and Oil Palm Empty Fruit Bunches (TKKS) whose raw materials were taken from the Cattle-Palm Integration System on changes in soil chemical properties and content of N. P, K and Mg palm plants. This study used a Completely Randomized Block Design (RAK) with one factor and 6 treatments, namely : F0 = Control (N,P,K,Mg), F1 = Cow dung only, F2 = 1/3 part of cow dung + 2/3 part of TKKS waste, F3 = 1/2 part of cow dung + 1/2 part of TKKS waste, F4 = 2/3 part of cow dung + 1/3 part of TKKS waste, and F5 = Only TKKS waste. The results showed that the bokashi residue of a mixture of cow dung and oil palm empty fruit bunches had a very significant effect on changes in soil pH, and no significant effect on changes in soil Al-dd, nutrient content of N, P, K, and Mg of immature oil palm plantations. The control treatment (F0), namely the use of chemical fertilizers NPK and Mg showed the smallest change in soil pH and was significantly different from other treatments in all tested formulas. Changes in NPK and Mg elements did not show any effect of giving bokashi but there was a tendency to add nutrients to the bokashi treatment which showed that the residue of bokashi mixture of cow dung and empty oil palm fruit bunches was able to last up to 24 months after application. It is recommended to re-apply bokashi a mixture of cow dung and oil palm empty fruit bunches on immature oil palm plants every 2 years.